RELATIONSHIP BETWEEN MATERNAL FIRST DAY POSTPARTUM BODY MASS INDEX AND LOW BIRTH WEIGHT NEONATE AT SANGLAH PUBLIC GENERAL HOSPITAL ON SEPTEMBER UNTIL NOVEMBER 2014 - Riszkia, Tasa; Hariyasa Sanjaya, I Nyoman (Bali Journal of Medical and Health Sciences; Vol 1 No 1 (2017): volume 1 no 1 Januari 2017, 2017)
Maternal nutritional status plays crucial role to ensure maternal and fetal well-being. The method that often used to determine someone’s nutritional status is by calculating the Body Mass Index (BMI). In developing countries, researches on the effects of body mass index on maternal and low birth weight neonate are still rare to be found, especially those using first day postpartum Body Mass Index. The aim of our study is to investigate the relationship between maternal first day postpartum body mass index and low birth weight neonate at Sanglah Public General Hospital on September until November 2014. This analytic observational study with cross sectional method used primary and secondary datas which have been taken from patient’s labor medical records in Sanglah Public General Hospital on September until November 2014. The samples are mothers who gave birth and were treated in Bakung Timur, Sanglah Public General Hospital who fulfilled the inclusion and the exclusion criteria. The data were described in the form of frequency tables and tested using a comparative test, Fisher Exact test. From 50 samples, there are 3 samples with low BMI (6%), 16 samples with normal BMI (32%), 12 samples with overweight BMI (24%), 14 samples with obesity I BMI (28%), 5 samples with obesity II BMI (10%). There are 6 neonates with LBW (12%), 42 neonates with NBW (84%), and 2 neonates with HBW (4%). On mothers with obesity II BMI, there are 5 neonates with NBW (100%). On mothers with obesity I BMI, there are 1 neonate with LBW (7.1%), 12 neonates with NBW (85.7%), and 1 neonate with HBW (7.1%). On mothers with overweight BMI, there are 1 neonate with LBW (8.3%), 10 neonates with NBW (83.3%), and 1 neonate with HBW (8.3%). On mothers with normal BMI, there are 2 neonates with LBW (12.5%) and 14 neonates with NBW (87.5%). On mothers with low BMI, there 2 neonates with LBW (66.7%) and 1 neonate with NBW (33.3%). By using Fisher exact test, the p value is less than the predetermined significance level (?= 0.05), it is 0.035. There is correlation between maternal first day postpartum BMI and low birth weight neonate. kaywords:body mass index, low birth weight, first day postpartum